2018
DOI: 10.31661/jbpe.v0i0.830
|View full text |Cite
|
Sign up to set email alerts
|

Medical Image Fusion using BEMD and an Efficient Fusion Scheme

Abstract: Background: Medical image fusion is being widely used for capturing complimentary information from images of different modalities. Combination of useful information presented in medical images is the aim of image fusion techniques, and the fused image will exhibit more information in comparison with source images.Objective: In the current study, a BEMD-based multi-modal medical image fusion technique is utilized. Moreover, Teager-Kaiser energy operator (TKEO) was applied to lower BIMFs. The results were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In this study, we have used BEMD for texture analysis (Faust, Acharya, et al, 2018; Mozaffarilegha et al, 2020), because this method can extract global structure even when fractals are present (Chen & Jeng, 2014). The data was examined in an adaptive time–frequency–amplitude space which accommodates non‐linear and non‐stationary image texture.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we have used BEMD for texture analysis (Faust, Acharya, et al, 2018; Mozaffarilegha et al, 2020), because this method can extract global structure even when fractals are present (Chen & Jeng, 2014). The data was examined in an adaptive time–frequency–amplitude space which accommodates non‐linear and non‐stationary image texture.…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of BEMD for texture extraction demonstrated that when it comes to extracting texture features, no other method performs adequately for all image types besides BEMD [13]. In this research, textural picture data was analyzed using the BEMD technique, in which the data was divided into intrinsic mode functions (IMFs), and the feature vectors were produced using fractal dimensions [14] [15].…”
Section: Texture Analysis Of Citrus Leaf Images Using Bemd For Huangl...mentioning
confidence: 99%
“…A block diagram of this system is shown in fig.9. fusion techniques such as HIS, DWT, LWT, PCA, NSCT and SIST in the era of color distortion and spatial information [16]. Fig.10.…”
Section: Review Of Related Researchmentioning
confidence: 99%
“…Fig.10. Schematic diagram of the BEMD-based medical image fusion method [16] In 2018 Bagheri and Saraf Esmaili also use the HMAX model for adaptive detection of liver disease in CT images. As illustrated in fig.11 their method consists of three steps: first using discrete wavelet transforms for noise removal and ROI selection, second extracting features by Gray-level Co-occurrence matrix and HMAX, for identifying recognition pattern and the last step, performance evaluation through K-fold method.…”
Section: Review Of Related Researchmentioning
confidence: 99%